Le stage en formation alternée dans l'enseignement supérieur : pour quel développement professionnel ? - Jérôme Eneau; Geneviève Lameul; Éric Bertrand
This research aims to analyze the professionalization process of Master students in an adult education program, based in the University of Rennes (Brittany). The material uses ten reflexive analysis papers, produced by the students for each end of their year session (Master 1 and Master 2). This reflexive production, which aims to formalize and clarify the articulation of theoretical and praxeological aspects of the Master program, shows the integrative experience acquired during the year. The analysis of these papers allows us to characterize the process of professional development from a model articulating three dimensions : 1) the identity dynamics linked with the process of professionalization, 2) the progressive professional socialization required by this professionalization, 3) the development of a specific posture, as a reflexive practitioner. The methodology employs a content analysis through inter-rater method. The results of this research offer a discussion on theoretical and practical levels, both for a better comprehension of professional development and for the trainers or program managers, to support this process of professionalization.